Factors associated with the high medication regimen complexity index in pediatric patients with chronic renal disease - Amanda M. PAIVA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: To determine the factors associated with the high medication regimen complexity in pediatric patients with chronic kidney disease. Methods: An observational, cross-sectional, descriptive and analytical study was conducted with patients treated at a multiprofessional outpatient clinic of a public teaching hospital. Data were collected from July to September 2019 from the medical record and pharmacotherapeutic follow-up form. The medication regimen complexity was the dependent variable and was assessed by the Medication Regimen Complexity Index. The independent variables were sex, age, number of diseases, number of medications, adherence to treatment and access to health services. The complexity was considered high when the the Medication Regimen Complexity Index was greater than 13.5 points. The association between the occurrence of high complexity of pharmacotherapy and the independent variables was performed using Pearson’s chi-square test and Fisher’s exact test. For univariate and multivariate analysis, the magnitude of the association was expressed by the odds ratio with a 95% confidence interval. Results: All patients treated during the study period were included in the study (n = 31). 67.7% of patients (n = 21) used at least four drugs, the same percentage presented complexity of high pharmacotherapy, being associated with the number of drugs used (p <0.001). The class of drugs, plus drugs that do not act on the cardiovascular system, 30% (n = 30). The most used medication by patients was sodium bicarbonate (n = 22; 70%). Conclusions: The high medication regimen complexity was associated with the number of drugs used and was observed in most patients studied, highlighting the importance of assessing the ICFT in children to optimize pharmacotherapy and, consequently, pediatric patient safety.